Development of internal shari'ah audit screening methodology based on maqasid al-shari'ah for takaful operations in Malaysia - Sheila Ainon Yussof (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2015)
Due to the proliferation of business scandals involving some large corporations worldwide, the internal audit (IA) function in many organizations today is designed to act as an effective tool to measure sound corporate governance; to support risk management; and ensure fraud awareness management. Recently in Malaysia, the IA function is given a greater role to play in ensuring Shari'ah -compliance and effective Shari'ah governance within IFIs. Takaful companies are now directed to adopt the SGF 2011 to ensure comprehensive compliance to Shari'ah and the TOF 2012 for operational efficiency and uniformity of Takaful practice. Stiffer penalties will be imposed on IFIs and its officers for not complying with Shari'ah under the new law, the IFSA 2013. With increasing growth of Shari'ah conscious consumers worldwide and the rising trend towards ethical financing and morally-guided behaviour, it will be prudent for Takaful companies in Malaysia to adopt a human-centric approach to audit and governance. Traditional audit benchmarks which measure organizational efficiency and profitability should be widened to include non-financial and socially responsible parameters like human welfare protection, where assessments are to be made on the beneficial impact of any laws, rules or regulations to stakeholders in order to achieve the higher objective of the Shari'ah (Maqasid al-Shari'ah) on social justice. This research examines the prospects and challenges of developing an internal Shari'ah audit model, designed to undertake a Maqasid-based internal audit of Takaful operations in Malaysia. It recommends the application of a screening methodology to measure social justice in its protection and wealth creating dimensions. The research also recommends a standardized internal Shari'ah audit framework (ISAF) for Takaful, as a move towards uniformity of audit practices, and a governing body to regulate the audit profession.